2002
DOI: 10.1071/ea00114
|View full text |Cite
|
Sign up to set email alerts
|

Industrial waste ferrogypsum — a substitute for gypsum to alleviate sodicity

Abstract: Ferrogypsum is a waste from the effluent treatment plant of the titanium industry located in Tuticorin in south India. It contains gypsum (526.3 g/kg) and iron (102.4 g/kg as Fe2O3). It does not contain any heavy metal at a detectable level. To evaluate ferrogypsum as a soil amendment to alleviate sodicity, a field experiment was conducted on a sodic soil (fine mixed non-calcareous isohyperthermic very deep Vertic Ustropepts) with rice as the test crop. There were 7 treatments consisting of ferrogypsum as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The gypsum application at a rate of 200-500 kg ha −1 significantly improved peanut yield [46]. Gypsum significantly enhanced the pod yield [47]. Also, gypsum at a rate of 500 kg per acre significantly increased the pod yield [48].…”
Section: Peanut Yieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gypsum application at a rate of 200-500 kg ha −1 significantly improved peanut yield [46]. Gypsum significantly enhanced the pod yield [47]. Also, gypsum at a rate of 500 kg per acre significantly increased the pod yield [48].…”
Section: Peanut Yieldsmentioning
confidence: 99%
“…Also, Kamara et al [28] reported that the highest filled pods were obtained with the calcium treatment. In addition, the dose of gypsum at 400 kg ha −1 significantly increased the quality traits of peanut [47]. The shelling percentage has been significantly increased by gypsum application [48].…”
Section: Peanut Quality Traitsmentioning
confidence: 99%
“…Incorporation of gypsum at depth (MacEwan et al 1992) and gypsum analogues (Jagadeeswaran et al 2002) have been used to stabilise sodic subsoils. Surface application of gypsum has also been demonstrated to increase the benefits of liming on acidity (Farina et al 2000a(Farina et al , 2000b.…”
Section: Sodicitymentioning
confidence: 99%